Peran Si’o dalam Perkawinan Adat Nias di Desa Marindal 1 Kecamatan Patumbak, Kabupaten Deli Serdang - Parera, Geby; Puspitawati Puspitawati (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2025)
This research is entitled "The Role of Si'o in Nias Traditional Marriage in Marindal I Village, Patumbak District, Deli Sedang Regency". The purpose of this research is to describe the duties and roles carried out by a Si'o in a series of Nias traditional marriage processions in Marindal 1 Village, and to identify and analyze the obstacles or challenges faced by a Si'o in carrying out his duties in the Nias traditional marriage procession in Marindal 1 Village. The method used is descriptive qualitative with data collection techniques through observation, in-depth interviews, and documentation. The results of the study show that Si'o plays a central role as a traditional figure who is responsible for bridging communication between two families. Si'o is not just an ordinary spokesperson, but an official representative of the family, especially from the male side, who has full responsibility to convey intentions, organize the handover of traditional symbols, and ensure that all stages of the traditional procession run in an orderly, sacred, and in accordance with the rules that have been passed down from generation to generation. To ensure the continued role of the Si'o in the future, efforts to preserve traditional customs are needed through several key steps, such as involving the younger generation in every traditional ceremony and utilizing modern technology, such as video documentation and digital media. This research utilizes Max Weber's leadership theory, specifically traditional leadership styles. The role of the Si'o is a concrete form of authority derived from cultural legitimacy. This research aims to understand the dynamics of wedding traditions in Nias. By examining the role of the Si'o, this research provides new insights into how customs adapt to the modern context and their impact on cultural identity.